Effects of the Vertical Component of Ground Motion on the Maximum-Inelastic-Horizontal-Response of SDOFs - Mousavi, Seyed Mohammad Fard; Sensoy, Serhan (World Scientific Publ Co Pte Ltd, 2023)
This study investigates potential effects of the vertical-component-of-ground-motion (VCGM) on the maximum-inelastic-horizontal-response (MIHR) of single-degree-of-freedom (SDOF) systems. The effects of VCGM can be considered in two categories. First, it may initiate some modes of failure, like over-compression, and second, it might adversely influence the horizontal response through altering the P-delta effect. The latter is a result of variation of the gravitational acceleration, and hence, seismic weight, upon action of the VCGM. This study uses time-history analysis to compare the response of SDOFs in presence and absence of the VCGM. In both cases, the P-delta effect is inherent in analyses and period-dependent feature of the stability-coefficient, which is essential for reliable treatment of the P-delta effect, is explicitly reflected. Since available record selection and scaling strategies use uncoupled vibrators in vertical and horizontal directions, this research follows two steps to avoid undesirable bias. The first step, which focuses on examining the influence of some important parameters, adopts an event-based record selection scheme. Results indicate that for certain combinations of the strength reduction factor and initial period of vibration the effect of the VCGM on the MIHR is significant. Specifically, the systems with initial periods between 1.0 and 2.0 s are found most vulnerable. Moreover, the mentioned effect is not limited to near source regions. The second step evaluates capability of the VCGM to initiate dynamic instability. In this step, a set of 26 records, which resembles an assumed target spectrum at a near field site, is used. Results show that under action of some of the examined records, the presence of the VCGM leads to dynamic instability; hence, this study suggests consideration of the VCGM for collapse evaluation.
Keywords: Vertical-component-of-ground-motion; P-delta effect; single degree of freedom system; stability coefficient; bi-axial excitation